MO879PROPOSAL OF A GERIATRIC ASSESSMENT TAILORED FOR OLDER CHRONIC KIDNEY DISEASE PATIENTS: RESULTS OF A PRAGMATIC CONSENSUS-BASED APPROACH. (29th May 2021) - Voorend, Carlijn; Joosten, Hanneke; Berkhout-Byrne, Noeleen; Diepenbroek, Adry; Franssen, Casper; Bos, Willem Jan W; Van Buren, Marjolijn; Mooijaart, Simon
Abstract: Background and Aims: Unidentified cognitive decline and other geriatric impairments are prevalent in older patients with advanced kidney disease. Despite guideline recommendation of geriatric evaluation, routine geriatric assessment is not common in these patients. While high burden of vascular disease and existing pre-dialysis care pathways mandate a tailored geriatric assessment, no consensus exists on which instruments are most suitable in this population to identify geriatric impairments. Therefore, the aim of this study was to propose a geriatric assessment, based on multidisciplinary consensus, for older people with advanced chronic kidney disease. Method: A pragmatic approach was chosen to reach agreement on a suitable set of instruments to routinely identify major geriatric impairments in older patients with advanced chronic kidney disease. This approach included focus group meetings to identify criteria for the assessment, literature review to identify potential instruments, questionnaire to inventory currently used instruments, an expert consensus meeting to ensure that the selection of tests was based on input from clinical experience in nephrology and geriatrics, and pilot testing to ensure practicability. In preparation of the consensus meeting we composed a project team and an expert panel (n=33), drafted selection criteria for the selection of instruments, and assessed potential instruments for the test-set. Results: Selection criteria related to general geriatric domains, clinical relevance, feasibility and duration of the assessment. The consensus-set contains instruments in functional, cognitive, psychological, somatic, patient preferences, nutritional status, and social domains (Figure 1 ). Administration of (seven) patient questionnaires and (ten) professional-administered instruments, by nurse (practitioners), takes estimated 20 and 40 minutes, respectively. Results are discussed in a multi-disciplinary meeting including at least nephrology and geriatric expertise, informing nephrology treatment decisions and follow-up interventions amongst which comprehensive geriatric assessment. Conclusion: This first multi-disciplinary consensus on nephrology-tailored geriatric assessment intent to benefit clinical care and enhance research comparability for older patients with advanced chronic kidney disease. The proposed geriatric assessment is currently implemented in multiple hospitals and studies. Future initiatives and studies should provide insights on effectiveness, feasibility, patient's satisfaction and, value for shared treatment decision making and outcome improvement.